Respuesta :

If s(x) = 2 – x^2 and t(x) = 3x
s(t) = 2-(3x)^2
(st)(-7)= 2-(3(-7))^2
(st)(-7)=2-(-21)^2
(st)(-7)=2-(441)
(st)(-7)= - 439.

thus the right option is -439

Answer:

(s*t)(-7)= 987

Step-by-step explanation:

s(x) =[tex]2 - x^2[/tex] and t(x) = 3x

WE need to find (s*t)(-7)

(s*t)(x) = s(x)* t(x)

s(x) =[tex]2 - x^2[/tex] and t(x) = 3x, plug in s(x) and t(x)

[tex](s*t)(x) = s(x)* t(x)= (2-x^2) * 3x= 6x - 3x^3[/tex]

To find (s*t)(-7) plug in -7 for x

[tex](s*t)(x) =6x - 3x^3[/tex]

[tex](s*t)(-7) =6(-7) - 3(-7)^3= 987[/tex]

The value of (s*t)(-7)= 987

ACCESS MORE